Effects of glycerin application on the hardness of nanofilled composite immersed in tamarind soft drinks - Titis Mustikaningsih Handayani; Raditya Nugroho; Lusi Hidayati; Dwi Warna Aju Fatmawati; Agus Sumono (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Loss of tooth structure is a consideration in the performance of restorative treatment involving nanofilled composite resins. Material polymerization factors and water absorption can affect the hardness of composite resins. Imperfect polymerization producing an oxygen inhibited layer (OIL) and causing water absorption can even compromise the hardness of nanofilled composite resins. Tamarind soft drink, on the other hand, has an acidic pH that compromises the hardness of nanofilled composite resins. Purpose: This study aimed to reveal the effects of glycerin application on the hardness of nanofilled composite resins immersed in tamarind soft drinks. Methods: The research constituted a laboratory experiment using 24 nanofilled composite resin samples with diameters of 5mm or 2mm, divided into six groups, namely: Group G, Group G AS 60, Group G AS 120, Group TG, Group TG AS 60, and Group TG AS 120. Glycerin was applied to the surfaces of three groups before curing, while the other three groups were not treated with glycerin. Finishing was subsequently conducted on all samples using a highspeed handpiece and superfine finishing bur, before they were polished with a low speed handpiece. The samples were then divided into specific groups, namely: a group with a 120-minute immersion time, a group with a 60-minute immersion time, and a group which was not immersed and maintained at a temperature of 37oC. Each sample was tested at three points using a Vickers hardness tester (VHT). Results: The results showed that the groups with glycerin had a higher hardness level than those groups. In addition, the non-immersed groups had a higher hardness level than those groups which were immersed. The one-way ANOVA test results confirmed that there was a statistically significant difference (p<0.05) between all groups. Conclusion: The application of glycerin to nanofilled composite resins immersed in tamarind soft drinks can increase their hardness levels.